Maintaining Peace : Implementation Of Religion Moderation in Mangli Hamlet, Pagertoyo Village - Roihanah Nafi’ah; Ghinadin Khalwa; Syahna Syalaisa Khoir; Azhar Pahlevi Rahman; Tsalitsa Saniyyah; Fitri (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Hamlet as the smallest unit in society is often a space for interaction for individuals with diverse religious backgrounds. Religious moderation plays an important role in building tolerance and mutual understanding among the community. This study aims to explore the application of religious moderation values in Mangli Hamlet by using qualitative methods through a phenomenological approach and descriptive design. The results showed that Mangli Hamlet, whose majority population is Muslim, implements various religious traditions such as Yasinan, Tahlilan, Dziba', and other similar activities routinely and has been going on for a long time. Although the majority is Muslim, this hamlet has succeeded in creating harmony with the Christian minority through interfaith cooperation in various activities, including celebrations and moments of mourning. This success is supported by the role of the hamlet head and the active participation of the community. The experience of Mangli Hamlet is clear evidence that religious moderation can be implemented to create a harmonious, just and inclusive life in a multicultural society.